Higher Oxidation State Organopalladium and Platinum Chemistry - Canty, Allan J.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2011)
Kyle A. Grice, Margaret L. Scheuermann and Karen I. Goldberg: Five-Coordinate Platinum(IV) Complexes.- Jay A. Labinger and John E. Bercaw: The Role of Higher Oxidation State Species in Platinum-Mediated C-H Bond Activation and Functionalization.- Joy M. Racowski and Melanie S. Sanford: Carbon-Heteroatom Bond-Forming Reductive Elimination from Palladium(IV) Complexes.- Helena C. Malinakova: Palladium(IV) Complexes as Intermediates in Catalytic and Stoichiometric Cascade Sequences Providing Complex Carbocycles and Heterocycles.- Allan J. Canty and Manab Sharma: h1-Alkynyl Chemistry for the Higher Oxidation States of Palladium and Platinum.- David C. Powers and Tobias Ritter: Palladium(III) in Synthesis and Catalysis.- Marc-Etienne Moret: Organometallic Platinum(II) and Palladium(II) Complexes as Donor Ligands for Lewis-Acidic d10 and s2 Centers.
Five-Coordinate Platinum(IV) Complexes -- The Role of Higher Oxidation State Species in Platinum-Mediated C-H Bond Activation and Functionalization -- Carbon-Heteroatom Bond-Forming Reductive Elimination from Palladium(IV) Complexes -- Palladium(IV) Complexes as Intermediates in Catalytic and Stoichiometric Cascade Sequences Providing Complex Carbocycles and Heterocycles -- h1-Alkynyl Chemistry for the Higher Oxidation States of Palladium and Platinum -- Palladium(III) in Synthesis and Catalysis -- Organometallic Platinum(II) and Palladium(II) Complexes as Donor Ligands for Lewis-Acidic d10 and s2 Centers.
Keywords: Chemistry; Chemistry, Organic; Catalysis; Chemistry; Organometallic Chemistry; Catalysis; Organic Chemistry